An Improved Neighbor Discovery Process in BLE 5.0 - Shan, Gaoyang; Choi, Geunkyoung; Roh, Byeong Hee; Kang, Jinsuk (2019 IEEE 10th Annual Information Technology, Electronics and Mobile Communication Conference, IEMCON 2019, 2019)
Two kinds of Neighbor Discovery Processes has been specified in BLE 5.0, namely basic and advanced neighbor discovery process. The neighbor discovery process enables a BLE device called a scanner to discover another neighboring BLE device called an advertiser. Advanced neighbor discovery process is an extended version of the basic one designed to accommodate environments where there are a large number of BLE advertisers. However, the advanced neighbor discovery process has a fatal drawback. That is the hidden node problem which makes it very difficult to discover an advertiser when more than two scanners try to discover the advertiser at the same time. Therefore, how to overcome this problem is a challenge. In this paper, we propose a solution that enables multiple scanners to discover an advertiser successfully. The proposed scheme can dynamically adapt to different numbers of scanners and achieve better discovery performance. The simulation results show the effectiveness of the proposed scheme.
Keywords: Bluetooth low energies (BLE); Extended versions; Hidden node problems; Internet of Things (IOT); Neighbor discovery; Advertising event; Bluetooth low energy (BLE); Internet of Things (IoT); Neighbor discovery process (NDP); Scanning